(untitled) (Conferencea, 2023)
In the process of analyzing this article, methods of logic, historicity, consistency and objectivity of scientific knowledge were widely used. An analysis was carried out on the state of social activity and forms of implementation in young people. Tursunova N.the educational guide of” social activity of young people: concepts and qualities " has been defined as a methodological resource to see our independent country among developed countries is the dream of every Uzbekistan. But it is not that this dream appeared yesterday or today. The increase in this desire in the hearts of our compatriots and the increased desire for the establishment of a new Uzbekistan, the increase in social activity, which we mentioned, was undoubtedly motivated by the fierce democratic reforms initiated by our President Shavkat Mirziyoyev